Role of Peace Education in Sustainability and Development of Pakistan - Haseeb, Faiza; Khan, Shahzad; Khan, Sajid; Alam, Arif; Shah, Ikram (International Journal of Economics and Financial Issues, 2020)
The study is based on AHP analysis to identify the feasibility of each level of schooling with respect to peace education. The AHP application presented, provided results of each relative factor or criteria to each respondent as well as the overall weightage for these criteria’s given by each individual/respondent in our study. The findings of the study revealed that, the dominant alternative for academic professionals and field experts that can play impressive role in peace education is the primary schooling, while the central criteria having influence on peace education are norms/values, followed by approaches/standards and knowledge/skills with respect to teacher’s judgements. On the other hand, significant factors/criteria for student’s choice with respect to peace education is approaches and standards. Students also prefer primary education level as the most effective stage for children to learn/catch peace education skills and adopt peace values. The quantification of impacting factors-like in our study are; knowledge/skills, approaches/standards and norms/values. Decision making with respect to peace building in young generation will play a significant role in achievement of sustainability in the peace. Therefore, at the grassroots level, providing trainings on peace education to the children in primary school can reduce risk of conflicts in Pakistan. The government and policy implementers should prioritize addition of peace education in devising curriculum and its implementation. Keywords; AHP, peace education, knowledge and skills, teachers, sustainability JEL Classifications: D74, I25, Q01 DOI: https://doi.org/10.32479/ijefi.10310